Spectrum of mitochondrial DNA deletions within the Common Deletion region induced by low levels of UVB irradiation of human keratinocytes in vitro - Hwang, Bor-Jang (2009)
We show that a single low-dose exposure of human epidermal keratinocytes (NHEK) to an FS20 light source in vitro can induce the formation of mitochondrial DNA deletions in a PCR detection assay. We used primer sets specifically designed to exclude amplification of segments containing the common deletion, but which could detect possibly lower abundance deletions generated within the same region of the mitochondrial genome. We characterized eight novel deletions of which six were generated from cut sites within, or adjacent to, short direct repeats. Two deletions involved cut sites in inverted tetrameric repeats; one of these also involved an insertion.